PENGARUH PEMBELAJARAN BERBASIS GAME EDUKATIF “COSMIC KIDS” TERHADAP KEMAMPUAN SAINS PADA ANAK USIA DINI - Anisa Dwi Lutfia; Yaswinda; Dadan Suryana; Nur Hazizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low scientific abilities of early childhood children due to less interesting and teacher-centered learning activities. To overcome this problem, learning media such as Cosmic Kids, an educational game, can foster children's interest in science. The purpose of this study was to determine the effect of Cosmic Kids educational game-based learning on the scientific abilities of early childhood children in Sitiung 1 Public Kindergarten. This quantitative research applied a quasi-experimental design. Group B of Sitiung 1 Public Kindergarten consisting of 10 students will be the subjects of the study in the 2025–2026 academic year. The author collected 20 students in grades B2 and B3, with 10 students in grade B2 and 10 students in grade B3 respectively. To collect data, an observation sheet instrument was used to observe children's scientific abilities. To analyze the data, the SPSS version 23 program for Windows used the t-test. The results showed that the Cosmic Kids educational game can improve children's scientific abilities at an early age. The t-test, which shows a sig value (2-tailed) of 0.000 < 0.05, explains that Cosmic Kids educational game-based learning has a significant effect on children's science abilities at an early age. As a result, Ha is accepted and Ho is rejected, that means Cosmic Kids educational game-based learning greatly influences the science abilities of early-age students at TK Negeri 1 Sitiung.